Using high pressure to investigate the stability of a high entropy wurtzite structured (MnFeCuAgZnCd)S - Mark A. Buckingham; Joshua J. Shea; Kho Zhi Quan; Pok Man Ethan Lo; Joshua Swindell; Weichen Xiao; David J. Lewis; Alex S. Eggeman; Simon A. Hunt (Communications Chemistry)
Abstract High entropy metal chalcogenides are an emergent class of materials that have shown exceptional promise in applications such as energy storage, catalysis, and thermoelectric energy conversion. However, the stability of these materials to factors other than temperature are as yet unknown. Here we set out to assess the stability of the high entropy metal sulfide (MnFeCuAgZnCd)S with high pressure (up to 9 GPa), compared to an enthalpically stabilised Ag3CuS2, and a quasi-stable (MnFeZnCd)S. Compression and pressure-annealing of (MnFeCuAgZnCd)S showed diffusion-controlled time and pressure dependent exsolution of jalpaite (Ag3CuS2) from the bulk. Bulk materials characterisation found minor phase impurities and possible elemental localisations in (MnFeCuAgZnCd)S prior to pressure-annealing. To gain deeper understanding of the material pre- and post-pressure annealing at the nanoscale an advanced technique was used which combined machine learning, unsupervised clustering analysis of STEM-EDX mapping with scanning precession electron diffraction (SPED), which revealed a chemically distinct post-pressure annealed jalpaite exsolved from (MnFeCuAgZnCd)S.